2015
DOI: 10.1017/s0305000915000057
|View full text |Cite
|
Sign up to set email alerts
|

The development of the causative construction in Persian child language

Abstract: The acquisition of systematic patterns and exceptions in different languages can be readily examined using the causative construction. Persian allows four types of causative structures, including one productive multiword structure (i.e. the light verb construction). In this study, we examine the development of all four structures in Persian child speech between the ages of 1;11 and 6;7, in correspondence with their caregivers' speech. We define developmental stages based on dendrograms derived from variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…A review of the structure of causatives and the similar, naturalistic child data used for K’iche’, Tzotzil, and Q’anjob’al indicates that the difference in the acquisition of causatives may be either due to structural and distributional differences between causatives in these languages, or due to the sampling or the type of analysis done in each language. Beyond Mayan languages, this study provides evidence for the potential for early acquisition of periphrastic causatives, unlike in Persian (Family & Allen, 2015), for instance. This suggests that children’s acquisition of causatives is not uniform, but conditioned by the language to which they are exposed, confirming the expectations of Bowerman (1988).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…A review of the structure of causatives and the similar, naturalistic child data used for K’iche’, Tzotzil, and Q’anjob’al indicates that the difference in the acquisition of causatives may be either due to structural and distributional differences between causatives in these languages, or due to the sampling or the type of analysis done in each language. Beyond Mayan languages, this study provides evidence for the potential for early acquisition of periphrastic causatives, unlike in Persian (Family & Allen, 2015), for instance. This suggests that children’s acquisition of causatives is not uniform, but conditioned by the language to which they are exposed, confirming the expectations of Bowerman (1988).…”
Section: Discussionmentioning
confidence: 71%
“…Studies on the acquisition of causatives have shown that children acquire the causative system of the language that they are exposed to, for example, Bowerman (1988). Family and Allen (2015), report that of the four types of causatives in Persian children initially acquire two types: lexical and light verb causatives. They start with the lexical causatives and progressively move to the light verb constructions.…”
Section: Causatives In Mayan Languagesmentioning
confidence: 99%
See 3 more Smart Citations